Reliability Analysis of Logic Network with Multiple Outputs - Zaitseva, Elena; Kvassay, Miroslav; Levashenko, Vitaly; Kostolny, Jozef (Communications - Scientific letters of the University of Zilina, 2015)
Reliability analysis of a logic network with multiple outputs is considered in this paper. One of the principal tasks of reliability engineering is identification of those system components that have the most influence on the system activity. There exist several measures that are used for this purpose. One of them is Structural Importance Measure (SIM) which focuses on topological importance of individual system components. This measure is calculated from the system structure function, i.e. function that defines dependency between system activity and activity of its components, using logical differential calculus. In this paper, we present a method that can be used to identify the structure function of a logic network with multiple outputs and, based on logical differential calculus, we propose several definitions of the SIM for this type of systems. As a case study, the topological analysis of a one-bit full adder is considered in the last part of this paper. This study demonstrates usefulness of our approach in reliability analysis of logic networks and indicates that its further development and practical implementation could be beneficial.